On the Blueshift of the Andromeda Galaxy - Harutyunian, H. A.; Torosyan, A. A.
The observed spectral shift of galaxies is usually interpreted using the Doppler effect. However, attention should be paid to other possible mechanisms of spectral shift. For example, suppose baryon matter evolves due to interaction with the carrier of dark energy. In that case, the objects that pass through longer evolutionary paths compared to our galaxy will be blue-shifted for us. Since the evolutionary spectral shift is a rather weak effect, it can only be detected at small cosmological distances, where the redshift due to the expansion of the Universe is not very large. From this point of view, the Andromeda Nebula is undoubtedly an appropriate example. It is one of the main members of the Local Group of galaxies and has a small blueshift. Here we review observational data and theoretical generalizations in favor of interpreting the blueshift of our neighboring galaxy as an evolutionary effect.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture